Նամակագրության, հեռախոսային խոսակցությունների, փոստային, հեռագրական և այլ հաղորդումների գաղտնիության իրավունքը որպես անձի իրավական կարգավիճակի տարր - Ռուբեն Ափոյան (ՀՀ ԳԱԱ հրատ.)
Внедрение современных новейших технологий связи и бурный рост информационной инфраструктуры привели к необходимости нового восприятия правового характера и защиты права на неприкосновенность личной жизни, составной частью которого является закрепленное в статье 23 части 5 Конституции Республики Армения право каждого на тайну корреспонденции, телефонных переговоров, телеграфных и иных сообщений и связанного с этим правового статуса личности. The introduction of modern advanced technologies of communication and the rapid growth of information infrastructure led to the necessity of a new perception of legal nature and protection of privacy of personal life, part of which is registered in Article 23, part 5 of the Constitution of the Republic of Armenia- everyone’s right to secrecy of correspondence, telephone conversations, telegraph and other communications and related legal status of the individual.
Keywords: Law